2022
DOI: 10.1093/rpd/ncac204
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon (222rn) Measurements and Estimation of Annual Effective Dose in Mvangan Locality, South Cameroon

Abstract: The present work was aimed at measuring indoor radon activity concentrations in dwellings in Mvangan locality, South Cameroon, in order to assess the extent of measures that may be necessary for controlling public indoor radon exposure in this area. Measurements were carried out using passive solid-state nuclear track detectors (RADONAVA Inc., RadTrak2, Sweden) following ISO 11665-4 standard. Radon concentration ranged between 36 ± 20 and 150 ± 30 Bq m−3 with arithmetic and geometric means values of 64 ± 25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…A WHO survey in 36 countries found that almost all countries set reference levels for acceptable radon concentrations for existing housing between 200 Bq/m 3 and 400 Bq/m 3 . Some countries have developed different reference levels for new and existing buildings, with lower values set for new homes [13]. A national reference level of 100 Bq/m 3 is recommended to limit the individual risk.…”
Section: Discussionmentioning
confidence: 99%
“…A WHO survey in 36 countries found that almost all countries set reference levels for acceptable radon concentrations for existing housing between 200 Bq/m 3 and 400 Bq/m 3 . Some countries have developed different reference levels for new and existing buildings, with lower values set for new homes [13]. A national reference level of 100 Bq/m 3 is recommended to limit the individual risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesis testing was also carried out to statistically compare the mean values obtained for each participating CT facility [9][10][11]. The null hypothesis was that two compared data sets were drawn from the same population with the same mean (H0: µx -µy = 0), while the alternative hypothesis was that two compared data sets were drawn from different populations with different means (H1: µx ≠ µy).…”
Section: Journal Of Multidisciplinary Applied Natural Sciencementioning
confidence: 99%
“…Average annual human exposure (effective dose) to all natural radioactive sources is estimated to be 2.4 mSv, and about 52% of this exposure is caused by the inhalation of radon [7]. Many studies have been conducted worldwide to evaluate the radiation dose to inhabitants caused by radon [8][9][10][11]. Previous studies in the area of Kosovska Mitrovica have also shown increased indoor radon concentrations in dwellings, which the authors have indicated a radon-prone area [12][13][14].…”
Section: Introductionmentioning
confidence: 99%